MUSICAL FORM AND ANALYSIS OF SIGNIFICANT SONGS THROUGH CHINESE TRAISARANA BUDDHIST BAND IN CHON BURI PROVINCE - Limtaveekiettikul, Apichai (Mahidol Music Journal, 2024)
The objective of this research is to study the Musical Form and Analysis of Significant Songs through Chinese Traisarana Buddhist Band in Chon Buri Province. This is the qualitative research; a researcher has chosen two essential informants: experts of musicology and ethnomusicology, and Chinese musicians who have experiences, expertise, and relationship with the Chinese Music Ensemble. The researcher has collected information, connection, and presentation in a descriptive analysis. The results find that the Chinese Traisarana Buddhist Band has chosen four important songs for performing in Chinese funerals: Qing Poi Sian, Er Shi Si Xiao, Oi Nai Ti - Po Tha, and Ing Leng Kuai Chi Chio Po Kiao. Firstly, the forms are binary form and strophic form. The speed is andante in the simple time signature. Each phrase applies different sets of sounds, and its main set is Kung. The conjunct progression is conducted by the interval M2, and m3 while the disjunct progression is conducted by the internal P4, P5, M6, and m6. Progression applies main techniques consisting of characteristics of sounds, augmentation, diminution, sequence, variation, and repetition which also use non-chord tones. Secondly, the chord progression is different from each song, consisting of a circle chords progression, a parallel harmonic movement, modulation, diminished chord, and chromatic. Thirdly, the main structure of a rhythmic pattern has two repetitive rounds, which become the core rhythm of the whole song. The rhythmic pattern of each four bars consists of one round. Each round has two forms: simple duple meter, and simple quadruple meter. Most of the first round will be composed of quarter notes alternating between the eighth note while the second round will be composed of quarter notes merged with the developed notes.